Characterization of a Human Foamy Virus 170-Kilodalton Env-Bet Fusion Protein Generated by Alternative Splicing - Lindemann, Dirk (American Society for Microbiology, 1998)
Primate foamy viruses (FVs) express, in addition to the 130-kDa envelope protein, a 170-kDa glycoprotein, which reacts with antisera specific for the envelope and Bel proteins. We determined the exact nature of this 170-kDa glycoprotein by using the molecularly cloned human FV (HFV). Radioimmunoprecipitation analysis of 293T cells transfected with appropriate expression constructs by using antisera specific for the HFV Env, Bel1, and Bel2 proteins, as well as reverse transcription-PCR analysis of HFV-infected cells, demonstrated that this protein is an Env-Bet fusion protein that is secreted into the supernatant. However, it is only loosely associated, or not associated, with viral particles. gp170 is generated by an alternatively spliced Env mRNA using a splice donor and splice acceptor pair localized within the env open reading frame (ORF), which is normally used to generate Bel1 and Bet transcripts derived from the internal promoter within the env ORF. gp170 is expressed at a level 30 to 50% of the Env precursor gp130. However, it alone does not confer infectivity to HFV particles, because capsids derived from proviruses expressing only the gp170 were not released into the supernatant. In contrast, viruses derived from proviral clones deficient in gp170 expression showed similar in vitro infectivity and replication kinetics to wild-type virus. Furthermore, both types of viruses were inactivated to a similar extent by neutralizing sera, indicating that shedding of gp170 probably does not affect the humoral immune response in the infected host.